Compensation of On-call and Fixed-term Employment: the Role of Uncertainty - Marloes de Graaf-Zijl (Tinbergen Institute, 2005)
In this paper I analyse the use and compensation of fixed-term and on-call employment contracts in the Netherlands. I use an analytical framework in which wage differentials result from two types of uncertainty. Quantity uncertainty originates from imperfect foresight in future product demand. I argue that workers who take over part of the quantity uncertainty from the employer get higher payments. Quality uncertainty on the other hand originates from the fact that employers are ex-ante unable to fully observe a worker's ability and results in lower wages. Using a combination of propensity score and Mahalanobis matching I analyse wage differentials and find that on-call workers receive compensation for providing quantity flexibility. Compensation of fixed-term contracts on the other hand is dominated by the negative wage effect of quality uncertainty. I investigate whether this relation still holds after the 1999 policy change that had a substantial impact on the attractiveness of on-call and fixed-term workers from the employers' perspective. I find that the policy change has not only influenced the use of on-call and fixed-term contracts, but unintentionally also their compensation.
Keywords: J31; J40; C21; 330; temporary employment; wage differentials; uncertainty